Utility of viscoelastography with TEG 6s to direct management of haemostasis during obstetric haemorrhage: a prospective observational study. (August 2021) - Roberts, T.C.D.; De Lloyd, L.; Bell, S.F.; Cohen, L.; James, D.; Ridgway, A.; Jenkins, V.; Field, V.; Collis, R.E.; Collins, P.W.
Highlights: Low fibrinogen ≤2 g/L is the most common finding in severe obstetric coagulopathy. The TEG 6s device can be used to guide fibrinogen replacement. A threshold for recommending fresh frozen plasma (FFP) transfusion was not identified. Empiric infusion of FFP may be indicated for bleeding after fibrinogen correction. Low platelet count <75 × 10 9 /L is rare and laboratory full blood count should be used. Abstract: Background: The TEG 6s is an automated cartridge-based device with limited description of use in obstetric haemorrhage. The aim of this analysis was to describe the utility of TEG 6s in identifying abnormal laboratory results of coagulation and platelet count, and inform an interventional treatment algorithm for postpartum haemorrhage. Methods: A prospective observational cohort study of 521 women with moderate to severe obstetric haemorrhage (>1000 mL blood loss), including 372 women with at least one TEG 6s test. A non-pregnant control group was used for reference. TEG 6s test parameters Citrated Functional Fibrinogen (CFF), Citrated Kaolin TEG (CK) and Citrated Rapid TEG (CRT) were compared with paired laboratory tests of fibrinogen, PT/aPTT and platelet count, obtained during haemorrhage. Results: Among 456 TEG 6s tests, 389 were matched with laboratory coagulation results. The receiver operator characteristic area-under-the-curve (95% CI) for CFF amplitude by 10 min to detect Clauss fibrinogen ≤2 g/L was 0.95 (0.91 to 0.99) ( P <0.0001, sensitivity 0.74 and specificity 0.97 at ≤17 mm). False positives had median (IQR) Clauss fibrinogen of 2.4 (2.3–2.7) g/L. The CK-R time had some utility for detecting prolonged PT/aPTT, however a threshold for fresh frozen plasma transfusion was not established. A CRT maximum amplitude <57 mm, when CFF was ≥15 mm, identified four of eight samples with platelet count <75 × 10 9 /L. Conclusion: The TEG 6s CFF can be used to identify low fibrinogen during obstetric haemorrhage. A value to identify transfusion thresholds for PT/aPTT and platelets was not established, and laboratory results should continue to be used.